2013
DOI: 10.1371/journal.pone.0054153
|View full text |Cite
|
Sign up to set email alerts
|

Gestation Dependant Changes in Angiogenic Factors and Their Associations with Fetal Growth Measures in Normotensive Pregnancy

Abstract: BackgroundEarlier studies indicate that altered angiogenesis at birth is associated with poor birth outcome in women with preeclampsia. Now, we hypothesize that the progressive gestation dependant changes in markers of angiogenesis will be more useful to predict birth weight early even in a normotensive pregnancy. This study for the first time examines the association of gestation dependant changes in the levels of maternal angiogenic factors in addition to their levels in cord with birth weight.MethodNinety t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 48 publications
3
28
1
2
Order By: Relevance
“…Furthermore, it is reported that during the second trimester, the maternal PlGF levels are high and the maternal sFlt-1 levels are low, creating a proangiogenic state. 19,25 In women with PE, sFlt-1 appears to increase earlier in gestation and reach a higher level than it does in controls, possibly leading to altered placental growth and function.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, it is reported that during the second trimester, the maternal PlGF levels are high and the maternal sFlt-1 levels are low, creating a proangiogenic state. 19,25 In women with PE, sFlt-1 appears to increase earlier in gestation and reach a higher level than it does in controls, possibly leading to altered placental growth and function.…”
Section: Discussionmentioning
confidence: 99%
“…Our study design has been previously reported by us in normotensive women. 25 Among the 46 normotensive women and 35 women with PE who were enrolled, the first time point blood sample was obtained from 42 normotensive women and 35 women with PE, the second time point blood sample was obtained from 43 normotensive women and 25 women with PE and the delivery sample was obtained from 45 normotensive women and 24 women with PE. An umbilical cord blood sample was obtained from 46 normotensive women and 34 women with PE.…”
Section: Methods Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately no maternal PlGF levels at the end of pregnancy were available within our cohort. During pregnancy, PlGF reaches its peak around 31 weeks of gestation, after which it declines [7,22] . Around the time of delivery, levels of maternal PlGF are comparable with levels around 19 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%